Analysis of the Impact of KITE Facilities and Macroeconomic Variables on Export Performance - Evan Harlan; Masruri Muchtar (Buletin Ilmiah Litbang Perdagangan, 2025)
One of the government’s measures to boost exports in Indonesia is the provision of the Import Facilitation for Export (KITE) program. This study aims to fill a research gap, as previous studies have not distinguished between the two types of KITE facilities: KITE Exemption and KITE Refund. This study focuses on the KITE Refund facility because its settlement mechanism does not require businesses to export. The study aims to analyze the effects of the KITE facility, import value, Gross Domestic Product (GDP), inflation, and exchange rates on companies’ export performance. This study employs panel data regression analysis using the Panel-Corrected Standard Errors (PCSE) model. The data consist of quarterly data from 120 companies covering the period from 2018 to 2023. The results indicate that the independent variables have a significant simultaneous effect on the dependent variable. Partially, the KITE facility, import value, and GDP each have a positive effect on export value. Meanwhile, inflation and the exchange rate have no effect on export value. The implication is that the government can continue and expand the provision of the KITE facility, continue infrastructure development and equitable distribution to improve logistics cost efficiency, and formulate integrated fiscal and monetary policies in an effort to increase exports.